Twelve new records of Coral associated fish from the Saint Martin’s island based on morphometric and molecular approaches (Bangladesh Journal of Zoology, 2021)
The study was conducted to know the diversity of coral associated fishes of the Saint Martin Island from December 2017 to April 2019. A total of 46 coral associated marine fish species were recorded, among them 12 species; sunajtuLiughcliug , Lutjanus russellii, Parupeneus indicus, Siganus sutor, Thalassoma lunare, Gazza achlamys, Pomadasys andamanensis, Pomadasys kaakan, Lethrinus crocineus, Argyrosomus regius, Istigobius ornatus and Cryptocentrus cyanotaenia under six family were newly recorded from this Island. We assume that there are more species to be explored and need proper management strategy for conservation of coral reef and its associated biodiversity.Bangladesh J. Zool. 48(2): 253-262, 2020